"Real-world:" preservice teachers' research competence and research difficulties in action research. (17th April 2020) - Toquero, Cathy Mae Dabi
Abstract : Purpose: The purpose of this study is to provide an analysis of the teacher education program focused on the development of the research competence of the preservice teachers, difficulties they encountered in conducting action research and the need to provide them with realistic research opportunities. Design/methodology/approach: This qualitative study made use of data sources taken from observations, feedback sessions, presentations and follow-up written interview of 133 randomly selected preservice teachers. Findings: Findings reported that the multicultural preservice teachers have novice research skills and that the real-world application of their research skills developed their research competence. However, they encountered difficulties creating their action research, such as in the literature review and the research conceptualization. Research limitations/implications: Aside from the self-reported experiences of the students, the training on the action research mainly focused on the conceptualization, design formulation of interventions and proposal writing stage but were not implemented due to course constraints. Practical implications: This study can assist policymakers to integrate a mandatory research course as part of the curricular offerings and for the university to create space for students to practice their research skills based on real-life problems in the basic level institutions. Social implications: Understanding the challenges, difficulties, and basic competence in the research development of the preservice teachers would strengthen the research practice of the future teachers for evidence-based teaching in the schools. Originality/value: The limited literature focus on the development of research competence on teacher education students using action research, including the difficulties that university students experience in doing research based on a societal context.